Preventing mass hysteria about human metapneumovirus (HMPV): a call for accurate information - Ahmad, Eshan; Salman, Zain; Naveed, Alina (Journal of the Pakistan Medical Association, 2025)
We are writing this letter to highlight a pressing issue concerning the recent outbreak of HMPV cases in China which has sent shockwaves across the world. The purpose of this letter is to underscore the pressing need to prevent an infodemic, which could lead to mass hysteria and panic as seen during the COVID pandemic. Human metapneumovirus (HMPV) is a significant respiratory pathogen that infects most children by age five and can cause severe illness in young children, the elderly, and immunocompromised individuals (1,2). There is strong evidence to suggest HMPV is far less virulent than COVID-19 and that the clinical impact of HMPV infection did not change during the COVID-19 pandemic, suggesting HMPV is unlikely to cause a pandemic (3). Media sensationalism and unverified reports can exacerbate fear, creating a public health challenge in addition to the biological threat of the virus itself the COVID-19 pandemic has demonstrated how negative information spread through mass media can contribute to collective hysteria and potentially lead to policy errors (4). A repeat of this scenario must be avoided. It is crucial not to become complacent simply because the outbreak is presently confined to just China and that Pakistan currently has an insignificant number of cases of HMPV. A study analysing panic responses during the pandemic found that health anxiety levels were consistent regardless of location or exposure to COVID-19 patients (5). The researchers also identified a spectrum of panic consequences, ranging from indifference and paranoia to optimism and health consciousness, bringing the complex psychological impacts of the situation to light. The primary objective of this letter is to accentuate the importance of risk communication and community engagement. The general public must be reassured about the preventability of severe outcomes through proper hygiene measures, early recognition of symptoms, and timely medical care. In order to prevent needless anxiety among the populace and to promote well-informed decision-making, it is the responsibility of medical practitioners, researchers, and public health authorities to provide the public with clear, evidence-based information. The medical and scientific communities are well aware of the threat posed by infodemics and the role they play in creating widespread panic among the masses. Emphasising these steps can help counteract misinformation while maintaining trust in healthcare systems.